A self-regulated expiratory flow device for mechanical ventilation: a bench study - Lianye Yang; Ubbo F. Wiersema; Shailesh Bihari; Roy Broughton; Andy Roberts; Nigel Kelley; Mark McEwen (Intensive Care Medicine Experimental)
Abstract Introduction Unregulated expiratory flow may contribute to ventilator-induced lung injury. The amount of energy dissipated into the lungs with tidal mechanical ventilation may be used to quantify potentially injurious ventilation. Previously reported devices for variable expiratory flow regulation (FLEX) require, either computer-controlled feedback, or an initial expiratory flow trigger. In this bench study we present a novel passive expiratory flow regulation device. Methods The device was tested using a commercially available mechanical ventilator with a range of settings (tidal volume 420 ml and 630 ml, max. inspiratory flow rate 30 L/min and 50 L/min, respiratory rate 10 min−1, positive end-expiratory pressure 5 cmH2O), and a test lung with six different combinations of compliance and resistance settings. The effectiveness of the device was evaluated for reduction in peak expiratory flow, expiratory time, mean airway pressure, and the reduction of tidal dissipated energy (measured as the area within the airway pressure–volume loop). Results Maximal and minimal reduction in peak expiratory flow was from 97.18 ± 0.41 L/min to 25.82 ± 0.07 L/min (p < 0.001), and from 44.11 ± 0.42 L/min to 26.30 ± 0.06 L/min, respectively. Maximal prolongation in expiratory time was recorded from 1.53 ± 0.06 s to 3.64 ± 0.21 s (p < 0.001). As a result of the extended expiration, the maximal decrease in I:E ratio was from 1:1.15 ± 0.03 to 1:2.45 ± 0.01 (p < 0.001). The greatest increase in mean airway pressure was from 10.04 ± 0.03 cmH2O to 17.33 ± 0.03 cmH2O. Dissipated energy was significantly reduced with the device under all test conditions (p < 0.001). The greatest reduction in dissipated energy was from 1.74 ± 0.00 J to 0.84 ± 0.00 J per breath. The least reduction in dissipated energy was from 0.30 ± 0.00 J to 0.16 ± 0.00 J per breath. The greatest and least percentage reduction in dissipated energy was 68% and 33%, respectively. Conclusions The device bench tested in this study demonstrated a significant reduction in peak expiratory flow rate and dissipated energy, compared to ventilation with unregulated expiratory flow. Application of the device warrants further experimental and clinical evaluation.